QUYI AMUDARYO IQTISODIY RAYONIDA ZIYORAT TURIZMINI RIVOJLANTIRISHNING IJTIMOIY-GEOGRAFIK JIHATLARI - Bekmetova, Sh.H.; Aminov, B.B. (SCIENCE and SOCIETY, 2024)
This article aims to study socio-geographical aspects that shaped the evolution of pilgrimage tourism in the Lower Amudarya Economic Region. It discusses the main religious and cultural monuments that have attracted pilgrims to the region, the demographic and ethnic factors that influence the pattern of pilgrimage, and the ways in which the natural landscape of the region has helped and limited the development of this type of tourism. In addition, the article examines the socio-economic impact of pilgrimage tourism on local communities, as well as the challenges and opportunities for further development of this industry.